Implementasi Model CLIS Untuk Meningkatkan Hasil Belajar Siswa pada Materi Suhu dan Perubahannya - Indriyani Bidara Kansil; Dewi Diana Paramata; Tirtawaty Abdjul (GRAVITY EDU : Jurnal Pembelajaran dan Pengajaran Fisika, 2021)
This study aims to improve students learning outcomes in temperature and its change material thought the implementation of children learning in science model. This research is a classroom action research using Kemmis and Taggart model with two cycles, and each cycle consists of planning, implementation, observation, and reflection. The subjects of this research are students in grade VIIB of SMP Negeri 5 Kota Gorontalo in the 2019/2020 academic year consist of 30 student. The result shows that the implementation of children learning in science model can improve students learning outcomes, which in cycle 1 the percentage of learning completeness is still low and has increased cycle II. For the teacher activity, the total value in every aspect obtained in cycle I is 76,7% and increased in cycle II to 83,4%, aspect of students activity in cycle I with the percentage of 9,67% whereas in cycle II has increased to 9,81%, and the percentage of student learning outcomes has increased in cycle I and cycle II which is from 66,6 % to 96%. For the reasons , it can be concluded that the implementation of children learning in science model is able to improve students learning outcomes. Keywords : Children Learning in Science (CLIS) Model, and Students Learning Outcomes.